The First Observation of Domoic Acid in Plankton Net Samples from the Sea of Marmara, Turkey - (:unkn) unknown (SPRINGER, 2016)
This study reports the first evidence of domoic acid (DA), an algal neurotoxin produced by the genus Pseudo-nitzschia, from plankton net samples collected in the Sea of Marmara in December, 2010 and February, 2011. DA concentrations of plankton net samples were analyzed by high-performance liquid chromatography (HPLC), using the fluorenylmethoxycarbonyl fluorescence derivatization technique (detection limit 0.2 ng DA). The biotoxin concentrations in samples from coastal waters varied between 0.96 and 5.25 mu g DA/mL. We also investigated possible correlations between physicochemical parameters and DA concentration. The DA levels appear to be correlated negatively with silica and nitrite concentrations for both sampling periods. These data may be used to evaluate the probability of finding similar conditions in coastal waters of the Sea of Marmara in order to determine the potential risks to local aquaculture and fisheries.
Keywords: Domoic acid; Seawater; Sea of Marmara; HPLC-FLD analysis; PERFORMANCE LIQUID-CHROMATOGRAPHY; DIATOM NITZSCHIA-PUNGENS; PSEUDO-NITZSCHIA; PHYTOPLANKTON; CALIFORNIA; COMMUNITY; SHELLFISH; SEAWATER; TOXIN; COAST